DEFORMATION BEHAVIOUR OF GELLAN GUM BASED ARTIFICIAL BONE STRUCTURES UNDER SIMULATED PHYSIOLOGICAL CONDITIONS - Nela Krčmářová; Jan Šleichrt; Tomáš Fíla; Petr Koudelka; Daniel Kytýř (Acta Polytechnica CTU Proceedings)
The paper deals with investigation of deformation behaviour of gellan gum (GG) based structures prepared for regenerative medicine purposes. Investigated material was synthesized as porous spongy-like scaffold reinforced by bioactive glass (BAG) nano-particles in different concentrations. Deformation behavior was obtained employing custom designed experimental setup. This device equipped with bioreactor chamber allows to test the delivered samples under simulated physiological conditions with controlled flow and temperature. Cylindrical samples were subjected to uniaxial quasistatic loading in tension and compression. Material properties of plain GG scaffold and reinforced scaffold buffered by 50wt% and 70wt% BAG were derived from a set of tensile and compression tests. The results are represented in form of stress-strain curves calculated from the acquired force and displacement data.